A manufacturing and annealing protocol to develop a cold-sprayed Fe-316L stainless steel biodegradable stenting material. (November 2019) - Frattolin, Jennifer; Roy, Ranjan; Rajagopalan, Sriraman; Walsh, Michael; Yue, Stephen; Bertrand, Olivier F.; Mongrain, Rosaire
Graphical abstract: Abstract: Biodegradable stents show promise to revolutionize coronary artery disease treatment. Its successful implementation in the global market remains limited due to the constraints of current generation biodegradable materials. Cold gas dynamic spraying (CGDS) has been proposed as a manufacturing approach to fabricate a metallic biodegradable amalgamate for stent application. Iron and 316L stainless steel powders are combined in a 4:1 ratio to create a novel biomaterial through cold spray. Cold spray processing however, produces a coating in a work hardened state, with limited ductility, which is a critical mechanical property in stent design. To this end, the influence of annealing temperature on the mechanical and corrosion performances of the proposed Fe-316L amalgamate is investigated. It was found that annealing at 1300 °C yielded a complex material microstructure, with an ultimate tensile strength of approximately 280 MPa and ductility of 23%. The static corrosion rate determined at this annealing temperature was equal to 0.22 mg cm −2  day −1, with multiple corrosion species identified within the degradation layers. Precipitates were observed throughout the microstructure, which appeared to accelerate the overall corrosion behaviour. It was shown that cold-sprayed Fe-316L has significant potential to be implemented in a clinical setting. Statement of Significance: Biodegradable stents have potential to significantly improve treatment of coronary artery disease by decreasing or potentially eliminating late-term complications, including stent fracture and in-stent restenosis. Current generation polymer biodegradable stents have led to poorer patient outcomes in comparison to drug-eluting stents, however, and it is evident that metallic biomaterials are required, which have increased strength. To this end, a novel iron and stainless steel 316L biomaterial is proposed, fabricated through cold-gas dynamic spraying. This study analyses the effect of annealing on the Fe-316L biomaterial through corrosion, mechanical, and microstructural investigations. The quantitative data presented in this work suggests that Fe-316L, in its annealed condition, has the mechanical and corrosion properties necessary for biodegradable stent application.